Microvascular Inflammation of the Renal Allograft: A Reappraisal of the Underlying Mechanisms - Lebraud, Emilie; Eloudzeri, Maëva; Rabant, Marion; Lamarthée, Baptiste; Anglicheau, Dany (Frontiers in Immunology, 2022)
Antibody-mediated rejection (ABMR) is associated with poor transplant outcomes and was identified as a leading cause of graft failure after kidney transplantation. Although the hallmark histological features of ABMR (ABMRh), i.e., microvascular inflammation (MVI), usually correlate with the presence of anti-human leukocyte antigen donor-specific antibodies (HLA-DSAs), it is increasingly recognized that kidney transplant recipients can develop ABMRh in the absence of HLA-DSAs. In fact, 40-60% of patients with overt MVI have no circulating HLA-DSAs, suggesting that other mechanisms could be involved. In this review, we provide an update on the current understanding of the different pathogenic processes underpinning MVI. These processes include both antibody-independent and antibody-dependent mechanisms of endothelial injury and ensuing MVI. Specific emphasis is placed on non-HLA antibodies, for which we discuss the ontogeny, putative targets, and mechanisms underlying endothelial toxicity in connection with their clinical impact. A better understanding of these emerging mechanisms of allograft injury and all the effector cells involved in these processes may provide important insights that pave the way for innovative diagnostic tools and highly tailored therapeutic strategies.